2008
DOI: 10.1089/acm.2008.0305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noninvasive Interactive Neurostimulation on Symptoms of Osteoarthritis of the Knee: A Randomized, Sham-Controlled Pilot Study

Abstract: Objective To explore the effects of noninvasive interactive neurostimulation used as an adjunct to usual care, on pain and other symptoms in adults with osteoarthritis of the knee. Design Randomized, sham-controlled trial. Setting A university in the southern United States. Subjects Thirty-seven (37) adults with knee osteoarthritis (based on American College of Rheumatology diagnostic criteria). Interventions Seventeen (17) noninvasive interactive neurostimulation (active or sham) sessions over 8 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…19 It is difficult to reconcile the negative findings of our study with published reports of reduced pain, increased pain threshold, or improved functional scores in NP patients in response to treatment with the InterX or a similar device-the ENAR (Electro Neuro Adaptive Regulator). [20][21][22] According to 1 report, after twelve 15-minute sessions with ENAR over a 6-week period, patients reported a significant reduction in the intensity of NP and improved NDI and Patient-Specific Functional Scale (PSFS) scores measured up to 24 weeks post-treatment. 22 In agreement with our findings, Schabrun et al 7 reported no changes in pain or NDI scores in their study of InterX effects on patients with chronic NP, although improvements in the Patient-Specific Functional Scale scores were observed 5 days after a single 10-minute application of InterX.…”
Section: Discussionmentioning
confidence: 99%
“…19 It is difficult to reconcile the negative findings of our study with published reports of reduced pain, increased pain threshold, or improved functional scores in NP patients in response to treatment with the InterX or a similar device-the ENAR (Electro Neuro Adaptive Regulator). [20][21][22] According to 1 report, after twelve 15-minute sessions with ENAR over a 6-week period, patients reported a significant reduction in the intensity of NP and improved NDI and Patient-Specific Functional Scale (PSFS) scores measured up to 24 weeks post-treatment. 22 In agreement with our findings, Schabrun et al 7 reported no changes in pain or NDI scores in their study of InterX effects on patients with chronic NP, although improvements in the Patient-Specific Functional Scale scores were observed 5 days after a single 10-minute application of InterX.…”
Section: Discussionmentioning
confidence: 99%
“…Selfe et al. (7) found that non‐invasive interactive neurostimulation scored better than a sham (no current) device for SF‐36 Vitality scale and patient global assessment, but not pain, in 37 patients with knee osteoarthritis. Gorodetskyi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Manufacturers claim that non‐invasive interactive neurostimulation relieves pain and promotes healing of various injuries (6). All three randomized controlled clinical trials published to date have demonstrated superiority for non‐invasive interactive neurostimulation over placebo (i.e., a no current sham device) for knee osteoarthritis (7), postoperative recovery from bone fractures (8) and operative reduction and internal fixation of bimalleolar, AO type B2 ankle fractures (9).…”
Section: Introductionmentioning
confidence: 99%
“…Major secondary efficacy end‐points included changes from baseline in (i) the responder rate in average OAPI to the end of the DB phase (16 weeks) or to the cutoff date, whichever was earlier; (ii) ≥ 30% or ≥ 50% improvement in average OAPI to the end of weeks 12 and 16; (iii) average OAPI and WOMAC 3.1 Global Score, and subscales (pain, stiffness and physical function) to the end of weeks 2, 4, 8, 12 and 16; and (iv) Patient Global Assessment (11‐point NRS, 0 = very good; 10 = very bad) score to the end of weeks 4 and 16. The sponsor adapted the wording from Patient Global Assessments used in other studies .…”
Section: Methodsmentioning
confidence: 99%